К вопросу о систематическом положении миоценовых газелей юга СССР - Короткевич, Е.Л. (Вестник зоологии, 1968)
The data obtained when studying the fossil bone remains 01 gazeile from hipparion fauna of vil. Belka, Odessa region (excavations of 1960-1966) and comparing this gazelle with gazelles from other locations of the South of the USSR and recent representatives of the genus Procapra and Gazella s. str. testify to the existance at least of two different groups of Neogenic gazelles in the given period in the mentioned territory. Some of these gazelles were characterized by elongated clinoid nasal bones, comparati-vely narrow forehead bones (interorbital width of their skull is greater than the distance between the external walls of the horn stumps), comparatively small acoustic bladders, a peculiar structure of the frontal edge of choanas and temporal bone the features approaching them to the recent gazelles of the genus Procapra Hodson, 1846. Other gazelles are characterized by more widely situated horn stumps, the distance between the external walls of which exceeds the interorbital width of the skull, by bigger acoustic bladders, another structure of the front edge of choanas and temporal bone and, probably, shorter nasal bones with a hollow on the front edge— the features approaching them to gazelles of the genus Gazella Blainville, 1816. However in the both groups of fossil gazelles there are primitive peculiarities of skull and extremity structure distinguishing them from the recent gazelles. Later on, with accumulation of facts it would be necessary, probably, to distinguish the tribes Gasellini into separate subgenera of the above-mentioned genera.